A Standalone and Quantitative Point‐of‐Need Testing Platform with Manual Readout Capability Based on Smart Hydrogel Strands - Saeed Boroomand; Navid Farhoudi; Christopher F. Reiche; Jules J. Magda; Florian Solzbacher; Lars B. Laurentius (Advanced Sensor Research)
Abstract Smart hydrogels hold great promise as sensing elements that can be tailored to respond to a wide array of biomarkers and can be integrated with different readout modalities. However, a major challenge with these sensors is response time, which depends on the hydrogel swelling behavior and is limited by diffusion. While geometrical miniaturization can accelerate response time, it often requires complex readout systems to detect volume changes, which is detrimental for use in point‐of‐need (PoN) applications. This study introduces a novel approach for hydrogel‐based platforms that realizes important PoN requirements such as sensitivity, cost‐effectiveness, instrument‐free, and fast response time. The proposed sensing mechanism involves constraining a hydrogel strand at both ends and utilizing a visually observable buckling behavior instead of directly measuring a volume change. The sensing principle is validated by measuring glucose, an important biological analyte, and examines measurement repeatability, response time, sensitivity, and dynamic range. The performance is also demonstrated in blood and serum. The effects of design parameters such as strand length and diameter on sensor performance are also investigated. This new sensor offers a straightforward visual readout without requiring complex instrumentation, paving the way for more accessible and affordable PoN devices.